Comparison study on chebyshev and composite lowpass filter for harmonic rejection in two ways radio - Liew, Hui Fang; Syed Idris, Syed Hassan (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.